INVESTIGATING THE ECONOMIC EFFICIENCY OF WASTE COLLECTION AND TRANSPORTATION –CASE STUDY FOR URBAN AND RURAL MUNICIPALITIES IN POLAND - Mariusz WALA; Piotr NOWAKOWSKI (Transport Problems, 2020)
Thisarticle presents the results of the analysis of waste collection in selected rural and urban municipalities in the Silesian Voivodship in Poland in the years 2014-2018. A new approach has been presented for the evaluation of the economic efficiency of the waste management system including all costs and revenues both for the local administration and the waste collection company in acircular economy context. The results include the impact of significant factors affecting the total cost of collection, which include transportation costs, personal costs, as well as administrative costs, including fees for using the environment and the fee for waste managementat the landfill. The mass from the separate collection increased for three municipalities from 2014,showing a positive impact of the new regulations considering secondary raw materials for recycling. In the five years of thestudy, the variable purchase prices of recyclable materials adversely affected the economic efficiency of the collection, which increased fees charged by municipalities to residents. The increase in costs was significant for the five years included in the study for a landfill fee increase of 40%, for an environmental fee increase of 15% and an increase of waste collection costs above20%. The main contribution of revenues is the waste collection fee from residents. As a consequence, the municipalities must increase waste collection fees. Due to a much larger number of waste categories and unstable purchase prices of secondary raw materials, waste-collecting companies should pay attention towardsreducing transport costs and using human resources more efficiently.